Antenatal depression and its relationship with birth outcomes and postnatal depression in Rural India: A longitudinal study - Deepak; Dhananjay W. Bansod; Anke Hoeffler (PLoS ONE, 2026)
Background Depression is the most common mental disorder among women of reproductive age, with maternal depression the second leading cause of morbidity worldwide. Despite the serious effects on both the mothers and their newborns, it is still a neglected issue. The purpose of this study is to explore the relationship between antenatal depressive symptoms, birth outcomes, and postnatal depression symptoms. Methods A community-based longitudinal survey was conducted among pregnant women in the rural Chatra district, Jharkhand, India, between April 2023 and February 2024. Participants were selected through multistage random sampling. We followed 246 pregnant women during their antenatal period (Phase I), and followed the same respondents (197 women) after the delivery (Phase II). The Four-Dimensional Symptom Questionnaire (4DSQ), translated into Hindi and validated by back-translation, was employed to assess depressive symptoms with strong internal consistency with Cronbach’s alpha = 0.94. Statistical analyses, including χ2 test and multivariate logistic regression, were performed to determine the association between antenatal depression (AND), birth outcomes, and postnatal depression (PND) at a 95% confidence interval, with odds ratios (OR) reported. Results The prevalence of antenatal depression was 56.05%, while postnatal depression was observed for 44.67% of the women. AND was significantly associated with caste category (OR= 4.459), mass media exposure (OR=2.392), family type (OR=3.252), multiple pregnancy (OR= 3.277), and intimate partner violence (OR= 4.424). However, no significant statistical association was found between AND and birth outcome (low birth weight (LBW), preterm birth). Birth outcomes, on the other hand, significantly contributed to PND, LBW (OR= 2.213), birth experience (OR=2.783), and family reaction to birth (OR= 4.323) being key factors. The sex of the child did not show a significant association with PND. Conclusion This study highlights the high prevalence of both AND and PND, as well as the strong association between birth outcomes and PND among women. Early detection and treatment of AND and PND are crucial for improving maternal mental health and infant development.